ANALISIS MENGENAI FAKTOR–FAKTOR YANG MEMPENGARUHI TINGKAT UNDERPRICED DI BURSA EFEK INDONESIA - FERRY SUHARDJO (Media Bisnis, 2015)
The aim of this study is to prove jointly influence of non-financial factors that consists of underwriter reputation, auditor reputation and life of the company as well as financial factors which consists of the percentage of shares held by existing shareholders, firm size, financial leverage, ROA and EPS affect the level of underpriced. Population company's initial public offering period of 1997 to 2004 at the Indonesia Stock Exchange as many as 133 companies. The sampling technique used in this research is purposive sampling method. Only the final sample of 90 companies. Non-financial factors that consists of stock underwriter reputation, auditor reputation and life of the company, as well as financial factors which consists of the percentage of shares still held by the existing shareholders, company size, financial leverage, ROA and EPS has no effect on a level underpriced.